The impact of trust in government on pandemic management on the compliance with voluntary COVID-19 vaccination policy among adolescents after social unrest in Hong Kong - Chung, Gary Ka-Ki; Chan, Yat-Hang; Chan, Siu-Ming; Chen, Ji-Kang; Wong, Hung; Chung, Roger Yat-Nork (Frontiers in Public Health, 2022)
Background The launch of COVID-19 vaccines among students provides an opportunity to re-open schools safely. Nonetheless, under the voluntary vaccination policy, the lack of trust in government since the unprecedented massive social unrest in Hong Kong may hinder the vaccination progress. This study aims to assess the impact of trust in government regarding pandemic management on the willingness, uptake, and intention of COVID-19 vaccination among students in Hong Kong. Methods Based on maximum variation sampling of 12 secondary schools of diverse socioeconomic background, 1,020 students aged 14–16 years completed an online survey between September and October 2021. Results 59.2% of the sample received at least one dose of the COVID-19 vaccine, 25.2% showed willingness of vaccination, 44.7% of the unvaccinated intended to receive the vaccine, whereas 13.4% were trustful to the government regarding pandemic management. Results from multivariable logistic regressions showed independent associations of trust with greater vaccination uptake [aOR = 1.63 (95% CI = 1.06–2.52), compared to distrust], willingness [aOR = 12.40 (7.72–19.93)], and intention [aOR = 4.49 (2.06–9.75)]. However, the impact of trust on vaccine uptake reversed [aOR = 0.53 (0.32–0.87)] after additional adjustment for the willingness of vaccination. Conclusion Students with higher trust in government regarding pandemic management tended to have greater vaccination willingness and hence uptake; nonetheless, given the same level of willingness, distrust might have facilitated a faster adoption of vaccination as a self-initiated protective behavior. As the level of trust is generally low among secondary school students in Hong Kong, rebuilding trust during adolescence is of importance for better preparedness of the next pandemic.